Answer:
<h2>The graph is in the attachment.</h2>
Step-by-step explanation:
The point-slope form of an equation of a line:
![y-y_1=m(x-x_1)](https://tex.z-dn.net/?f=y-y_1%3Dm%28x-x_1%29)
<em>m</em><em> - slope</em>
<em>(x₁, y₁)</em><em> - a point on a line</em>
The slope-intercept form of an equation of a line:
![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
<em>m</em><em> - slope</em>
<em>b</em><em> - y-intercept → (0, b)</em>
We have the equation in a point-slope form:
![y+7=-\dfrac{4}{5}(x-4)](https://tex.z-dn.net/?f=y%2B7%3D-%5Cdfrac%7B4%7D%7B5%7D%28x-4%29)
![y-(-7)=-\dfrac{4}{5}(x-4)](https://tex.z-dn.net/?f=y-%28-7%29%3D-%5Cdfrac%7B4%7D%7B5%7D%28x-4%29)
Therefore we have one point: <em>(4, -7)</em><em>.</em>
<em>Convert to the slope-intercept form:</em>
<em>use the distributive property</em>
![y+7=-\dfrac{4}{5}x+\left(-\dfrac{4}{5}\right)(-4)](https://tex.z-dn.net/?f=y%2B7%3D-%5Cdfrac%7B4%7D%7B5%7Dx%2B%5Cleft%28-%5Cdfrac%7B4%7D%7B5%7D%5Cright%29%28-4%29)
![y+7=-\dfrac{4}{5}x+\dfrac{16}{5}](https://tex.z-dn.net/?f=y%2B7%3D-%5Cdfrac%7B4%7D%7B5%7Dx%2B%5Cdfrac%7B16%7D%7B5%7D)
<em>subtract 7 from both sides</em>
![y=-\dfrac{4}{5}x-3\dfrac{4}{5}](https://tex.z-dn.net/?f=y%3D-%5Cdfrac%7B4%7D%7B5%7Dx-3%5Cdfrac%7B4%7D%7B5%7D)
Put <em>x = -1</em><em> </em>to the equation:
![y=-\dfrac{4}{5}(-1)-3\dfrac{4}{5}=\dfrac{4}{5}-3\dfrac{4}{5}=-3](https://tex.z-dn.net/?f=y%3D-%5Cdfrac%7B4%7D%7B5%7D%28-1%29-3%5Cdfrac%7B4%7D%7B5%7D%3D%5Cdfrac%7B4%7D%7B5%7D-3%5Cdfrac%7B4%7D%7B5%7D%3D-3)
Therefore we have the second point <em>(-1, -3)</em>.